HIV-related risk perception among female sex workers in Nigeria - Ankomah A (Dove Medical Press, 2011)
Augustine Ankomah1, Godpower Omoregie1, Zacch Akinyemi2, Jennifer Anyanti1, Olaronke Ladipo1, Samson Adebayo11Society for Family Health, Abuja, Nigeria; 2Population Services International, Kigali, RwandaBackground: Over one-third of sex workers in Nigeria are infected with human immunodeficiency virus (HIV), yet there is a lack of understanding of sex workers’ own perception of sexual risk-taking. Applying the theory of cognitive dissonance, this paper examined the personal HIV risk perception of brothel-based sex workers.Methods: The study is based on 24 focus group discussions held among brothel-based sex workers in four geographically and culturally dispersed cities in Nigeria.Results: It was found that sex workers underestimated their risk of infection and rationalized, defended, or justified their behaviors, a typical psychological response to worry, threat, and anxiety arising from the apparent discrepancies between beliefs and behaviors. To reduce dissonance, many sex workers had a strong belief in fatalism, predestination, and faith-based invulnerability to HIV infection. Many believed that one will not die of acquired immune deficiency syndrome if it is not ordained by God. The sex workers also had a high level of HIV-related stigma.Conclusion: From these findings, most sex workers considered risk reduction and in particular condom use as far beyond their control or even unnecessary, as a result of their strong beliefs in fatalism and predestination. Therefore, one critical area of intervention is the need to assist sex workers to develop accurate means of assessing their personal vulnerability and self-appraisal of HIV-related risk.Keywords: female sex workers, cognitive dissonance, risk perception, risky behavior, focus group discussions, Nigeria